(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Coronary artery disease (CAD) is a prevalent disease worldwide, and thus requires early and proper diagnosis. Computed Tomography Coronary Angiography (CTCA) has become a non-invasive diagnostic type which has high sensitivity in the diagnosis of coronary stenosis. But remains a diagnostic phenomenon dependent upon the patient heart rate, thus impacting on both the temporal resolution and images of the patient. This was done to establish the diagnostic accuracy of CTCA in patients with different categories of heart rate (≤60 bpm and >60 bpm) comparing invasive coronary angiography to be the gold standard. Methods: This is a cross-sectional validation study carried out in the Department of Cardiology of our Lady of Lourdes Hospital, Drogheda, Ireland between February and July of 2025. One hundred and thirty-five patients with clinical suspicion of CAD age 2575 years. All the patients underwent CTCA were not subjected to any prior treatment of controlling heart rate, then invasive coronary angiography was conducted. CTCA were regarded as positive when CAD was found at 50 percent luminal stenosis in one of the major epicardial arteries, and angiography diagnosis was CAD at 70 percent (or 50 percent in the left main artery). The data were analyzed using SPSS version 25, the parameters of diagnostic accuracy in 2×2 contingency tables were calculated. Results: Risk factors prevalent among 135 patients were hypertension (56.3%) and smoking (45.9%). The mean aga and heart rate were 52.4 ± 11.4 years and 69.7 ± 13.7 bpm respectively. CTCA had sensitivity 90.9%, specificity 87.0 and 88.9% of accuracy compared with invasive angiography. The CTCA had a better diagnostic quality in patients with heart rate less or equal 60 bpm (sensitivity 95.0, specificity 94.1, PPV 95.0, NPV 94.1, accuracy 94.6) but in the >60 bpm group these parameters were slightly lower (sensitivity 89.1, specificity 84.6, accuracy 86.7). Stratified analysis showed that there was excellent performance with CTCA at ≤60 bpm, irrespective of gender, age or comorbidity subgroups, but higher heart rate was related to high false-positive rates especially among younger males and hypertensive or diabetic patients. Conclusion: CTCA has very high diagnostic accuracy in the identification of the presence of substantial CAD with maximum accuracy observed at a heart rate of 60 bpm and below. The reduced heart rates reduce motion artifacts and improve coronary visualization leading to high sensitivity and specificity. Contrary to this, the high heart rates have a low effect on accuracy, mainly because of false-positives.